1993
DOI: 10.3109/08916939309014643
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Igf-1 Binding Sites in Thyroid Associated Ophthalmopathy

Abstract: Graves' disease is an autoimmune disorder but the nature of the association between hyperthyroidism and ophthalmopathy is not yet understood. Serum autoantibodies to orbital tissues have previously been identified and the cross-reactivity with orbital and thyroid antigens has been implicated in the development of thyroid-associated ophthalmopathy (TAO). The ophthalmopathy of Graves' disease is remarkable for the hypertrophy of extraocular muscles and proliferation of fibroblasts within the orbit; features whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 27 publications
2
83
0
Order By: Relevance
“…125 I]IGF-I could bind to orbital fibroblasts obtained from normal tissue (46). Twelve of 23 GDIgG preparations tested in that earlier study significantly displaced binding regardless of whether the donor manifested clinical TAO.…”
Section: Discussionmentioning
confidence: 78%
“…125 I]IGF-I could bind to orbital fibroblasts obtained from normal tissue (46). Twelve of 23 GDIgG preparations tested in that earlier study significantly displaced binding regardless of whether the donor manifested clinical TAO.…”
Section: Discussionmentioning
confidence: 78%
“…High circulating levels of this hormone indicate some endocrine role (16) . There is a paper (17) that demonstrated that IgG prepared from patients with Graves' disease with or without overt ophthalmopathy interact with IGF-1 binding sites on orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Other antigens besides TSHR have been examined for their potential involvement in TAO. Among them, the IGF-I pathway was first implicated in studies examining whether IgG from patients with Graves' disease (GDIgG) could displace 125 I-IGF-I from the surface of human fibroblasts (Weightman et al, 1993). Those studies demonstrated a dose-dependent competition with radiolabeled IGF-I from fibroblast surfaces.…”
Section: B Graves' Diseasementioning
confidence: 99%